TRAINING WRITING NONFICIAL STORIES IN STUDENTS OF THE PGSD STUDY PROGRAM WIDYA DHARMA KLATEN UNIVERSITY - sakti, bayu purbha (Universitas PGRI Yogyakarta, 2019)
Students of the Widya Dharma University Primary School Teacher Education (PGSD) Study Program are expected to have insight and knowledge in nonfiction story writing. News that is part of a nonfiction story favored by elementary school children. Writing news will familiarize PGSD students in writing activities and later they also have no difficulty in doing thesis. PGSD students who take part in the training are expected to excel in student-level writing competitions. The trainees were also reminded to maintain the authenticity of the news written. News must be reported by prospective elementary school teachers so that students, families, and communities can avoid Liar News / hoaxes.